Diagnóstico de la innovación y desarrollo tecnológico en el sector de la construcción de la ciudad de Ambato - De la Cruz Yunapanta, Edisson Javier (2024)
This research was carried out with the objective of carrying out an analysis to diagnose the level of innovation and technological development in the construction sector in the city of Ambato. Under a qualitative and quantitative approach, information was collected using a survey as an instrument, which was applied to a sample of 10 companies in the construction sector in the city of Ambato. The sampling used was non-probabilistic by convenience; in other words, the companies were selected based on the researcher's criteria and considering the accessibility and availability of the required information. By means of the innovation survey applied, it was possible to find out that all of these companies had factors that could favour them and others that represented a threat to their innovation and therefore put their permanence in the market at risk. Among the factors that required the most attention were the results, i.e. that they did not have solid foundations that generate confidence and demonstrate solidity to customers and competitors, indicating that there was a lack of discipline in the pursuit of innovation and in the long-term strategies initially proposed. It was also revealed that, aspects such as satisfaction in participating in innovation initiatives and the development of competencies in staff, are not considered a priority in these organisations.